Effects of Calcium (Ca), Phosphorus (P) and Manganese (Mn) Supplementation during Oil Palm Frond Fermentation by Phanerochaete chrysosporium on Rumen Fluid Characteristics and Microbial Protein Synthesis - Jamarun, Novirman; Zain, Mardiati; Arief,; Pazla, Roni (Pakistan Journal of Nutrition, 2017)
Objective: The aim of this study was to evaluate the effects of calcium (Ca), phosphorus (P) and manganese (Mn) supplementation during Oil Palm Frond (OPF) fermentation by Phanerochaete chrysosporium on rumen fluid characteristics and Microbial Protein Synthesis (MPS). Materials and Methods: This study was conducted using a randomized block design with 3 treatments (the addition of Ca, P and Mn) and 5 replications. The following treatments were performed: T1 = 2000 ppm Ca+1000 ppm P+150 ppm Mn, T2 = 2000 ppm Ca+1500 ppm P+150 ppm Mn and T3 = 2000 ppm Ca+2000 ppm P+150 ppm Mn. The data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan’s multiple range test for comparisons among the treatment means. The parameters measured were as follows: pH, Volatile Fatty Acids (VFAs) (mM), NH3 (mM), total protozoa (cells mL–1) (log 10), total bacteria (cells mL–1) (log 10) and MPS (mg mL–1). Results: The results revealed that VFA levels were significantly increased by the addition of P in T3. However, T1, T2 and T3 non-significantly affected (p>0.05) pH, NH3, total protozoa, total bacterial and MPS. Conclusion: The supplementation of OPFs with 2000 ppm Ca, 2000 ppm P and 150 ppm Mn resulted in the best rumen fluid characteristics and MPS.